The lionhearted - Savitz, Harriet May. (New York John Day Co., 1975)
Resigned to spending her life in a wheelchair, Rennie reaches out to new friendships with an overweight girl and a handsome, popular senior boy.
Keywords: People with disabilities -- Fiction